STRATEGI PENGELOLAAN PAJAK DAERAH DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH (PAD) KOTA BANJARMASIN - Eny Dewi (At-Taradhi Jurnal Studi Ekonomi, 2017)
This study aims to determine the effectiveness, efficiency and strategy of local tax management to increase the local receipt (PAD). The analysis technique used is descriptive analysis and SWOT analysis. The result of the research shows that the 2011-2015 average of effectiveness ratio of Banjarmasin City Local Tax is included in very effective category, so also efficiency ratio is in very efficient category. In detail the Local Taxes by type belonging to very effective categories include Hotel Tax, Restaurant Tax, Street Lighting Tax, Parking Tax, and Rural and Urban Land and Building Tax (PBB-PP). Fairly effective categories include Entertainment Tax and Advertising Tax, less effective category is a BPHTB tax, while the Swallow's Nest Tax is an ineffective category. Overall efficiency averages fall into the most efficient category, except the Tax on Land and Building Acquisition (BPHTB) and Rural and Urban Land and Building Tax (PBB-PP) which fall into the efficient category. Strategies to increase Local Receipt (PAD) are 1) to socialize and publicize services and public awareness of the importance of Local Taxes 2) Increase the use of better information technology so as to increase the capability in validation of tax potentials and levies more valid, 3) Simplify the bureaucratic stage and increase online services in terms of tax payments so as to attract public interest to pay taxes.Keyword: Local Receipt, Local Tax, Effectiveness Ratio, Efficiency Ratio